The educational attention of the students of the preparatory faculty from the improvement of the teacher - Venet Pérez , Maritza; Quesada Pita, Guadalupe de las Mercedes; Taño Hernández-Piloto, Herminia Carmen (Revista Minerva, 2021)
The University faces a number of challenges in a changing world. It demands the systematization of the mission and vision related to the historical context. The requirements address professional improvement and educational training of the student as a future professional. The purpose of the work is to reflect on the professional improvement for the educational attention of non-Spanish-speaking students of the Preparatory School.